2022
DOI: 10.33503/journey.v5i1.1818
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing Efl Learners’ Speaking Skills Through the Audio-Lingual Method

Abstract: The teaching method is one of the contributing factors to successful English language learning. The appropriate use of a teaching method is one of the ways to enhance learners’ speaking skills. The present study aims at reviewing the use of the Audio-Lingual Method (ALM), one of the teaching methods to enhance EFL learners’ speaking skills.      The present study employs library research to delineate the use of ALM to enhance learners' mastery of speaking skills. The data were obtained from documentation study… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 0 publications
0
8
0
Order By: Relevance
“…Moreover, the results of Nitami & Ardi, (2023), showed that teaching assistants through the MBKM program have significantly contributed to the participants' competencies for being a professional teacher. The findings of (Putra et al, 2022) revealed that teaching profession is a challenging profession because teachers should possess a number of requirements such as pedagogical knowledge, subject matter knowledge, organization and communication skills, and socio-affective skills. Meanwhile, (Jihan et al, 2023), state that teachers must be creative and innovative in teaching their students.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the results of Nitami & Ardi, (2023), showed that teaching assistants through the MBKM program have significantly contributed to the participants' competencies for being a professional teacher. The findings of (Putra et al, 2022) revealed that teaching profession is a challenging profession because teachers should possess a number of requirements such as pedagogical knowledge, subject matter knowledge, organization and communication skills, and socio-affective skills. Meanwhile, (Jihan et al, 2023), state that teachers must be creative and innovative in teaching their students.…”
Section: Discussionmentioning
confidence: 99%
“…Teaching is a challenging career because teachers must meet a number of requirements, including pedagogical knowledge, subject matter knowledge, organization and communication skills, and socio-affective abilities (Putra et al,2022). There is a lot of pedagogical knowledge that has to be mastered by the teacher, one of which is teaching strategy.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, when we speak, we create language, and that text should have a purpose. According to (Ashari Putra et al, 2022), speaking is regarded as one of the most crucial talents to master. The system can be separated into spoken and writing abilities based on the four language skills.…”
Section: Introductionmentioning
confidence: 99%